Social stability and efficiency wages : the case in the context of the Chinese labour market : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Business Studies in Economics at Massey University - Wu, Gezie George (Massey University, 1999)
Chinese gradual and piecemeal reform has generated dual labour market sectors: the state sector vs. the non-state sector. One important feature of reforms in the state sector is that balancing the objective of maintaining social stability against that of improving productivity is highlighted. In this thesis I suggest that this trade-off is inherent in the policy of xiagang which allows state owned enterprises to layoff workers but forces them to continue providing some wages and non-wage benefits. The aim of this thesis is to examine the relationship between social stability and a range of variables such as wages, effort levels, employment, output, productivity and profitability. To fulfill it, this thesis builds a theoretical model that extends the Shapiro and Stiglitz no-shirking efficiency wage model to include characteristics of the Chinese context. The most important innovation in this model is the introduction of a social stability parameter that reflects some key features of xiagang such as a low likelihood of workers being laid off. The likelihood of layoffs could be lowered in the interest of social stability. A comparative static analysis is undertaken on this model. It shows that with an increase of this social stability parameter, the overall wages, unskilled worker's effort levels and their employment tend to rise, but the overall profit levels and skilled worker's effort levels tend to decline; Skilled worker's employment, the overall output and productivity may either increase or decrease. This implies that profitability may be improved by lowering the social stability parameter, but that improvement is more likely to be realised through cutting labour costs at an expense of shifting more workers into xiagang rather than through improving the overall productivity.
Keywords: China; Wages and productivity; Industrial productivity; Labor market